Folquet de Marseille ou Foulques de Toulouse ? La mémoire d’un troubadour devenu évêque à travers ses représentations - Léa David (Bulletin du Centre d’Études Médiévales d’Auxerre)
The path of Fulk of Toulouse (1155-1231), main figure of southern France history, has been studied thanks to the many written sources that mention him : the images that represent him have not been studied yet. This article aims to fill this gap and analyse representations of the bishop Fulk of Toulouse in troubadours chansonniers of the second half of the 13th century. Six in number, they feature the character and mark the beginning of the section dedicated to his poems. Nearly fifty years after his death, they show the central importance of this character, whose memory is blurred by his atypical path, which led him in turn to be a troubadour, a monk, and a bishop.